Exploring the Relationship Between Stress, Burnout, and Occupational Accidents in Civil Construction - Tran, Anh Viet; Tran, Hung Van; Luong, Trung Thanh; Nguyen, Tuong N. C. (Emerging Science Journal, 2025)
This study investigates the factors influencing work-related stress, burnout, and occupational accidents in the civil construction sector. Using a mixed-methods approach, the research integrates both qualitative and quantitative methodologies. Measurement scales for stress, fatigue, and occupational accidents were reviewed, translated, and adapted from prior studies to suit the context of construction workers. A total of 275 questionnaires were distributed, with 269 valid responses analyzed using SmartPLS (ver 3.2.8). Data analysis encompassed evaluating the validity and reliability of scales and exploring the relationships among key concepts in the research model. The findings highlight the significant influence of job attributes, co-worker relationships, and work environment on work-related stress. These factors trigger psychological changes that exacerbate worker fatigue and contribute to increased occupational accident rates. Novel insights emphasize the interdependence of these elements in shaping worker behavior and safety outcomes. The study provides a foundation for developing targeted strategies to mitigate stress and fatigue, reduce occupational hazards, and promote well-being among construction workers. By offering an integrated analysis, this research contributes to advancing the understanding of safety management practices in the construction industry.